SMALL-SCALE SPATIAL PATTERNS OF TWO TERRICOLOUS LICHENS IN A CONIFER PLANTATION - Sevgi, E.; SEVGİ, ECE; Yilmaz, O. Y.; Sevgi, O. (My University, 2020)
Various studies have been conducted on the factors affecting the spatial distribution of terricolous lichen species at regional and landscape scales, yet not on small-scales. In our study, the distribution of lichens was obtained by objective classification and spatial analysis of RGB camera images taken from two different heights by an unmanned aerial vehicle at a reforested area of 1575 m(2). Black pine and cypress are species that have been introduced, while the, native species are oak and mock privet. The total area covered by Cladonia rangiformis Hoffm., (26.17 m(2)) in the study area was 5 times higher than that covered by the Cladonia foliacea (Huds.) Willd. (5.01 m(2)). These species were found to be located mostly to the north and sometimes at the east of the tree species. C. rangiformis was found under the crown projection area of cypress; however, no such result has been found for black pine, mock privet, and oak. Therefore, tree species affect the distribution of terricolous lichen species. The patch sizes of both of these lichen species fit the power law distribution and demonstrate inhomogeneous spatial distribution in the area. C. rangiformis and C. foliacea patch size classes generally clustered at short distance (2-2.5 meters) and demonstrated regular distribution beyond this distance.